A novel transformerless photovoltaic grid-connected current source inverter with ground leakage current elimination - Saeidabadi, Saeid; Gandomi, Amin Ashraf; Hosseini, Seyed Hossein (2017 8th Power Electronics, Drive Systems & Technologies Conference (PEDSTC), 2017)
A novel single-phase single-stage transformerless grid-connected current source inverter is proposed for photovoltaic system application. The proposed inverter consists of one inductor, four unidirectional switches and two diodes. The proposed inverter does not suffer from ground leakage current since that the PV panel and the gird utilize common ground. Also, the proposed inverter is capable of connecting the low voltage PV panels to the grid. A control method based on the hysteresis control method is also developed to apply sinusoidal current to grid and it can do maximum power point tracking (MPPT). In addition, a comparison of the proposed inverter with some common grid-connected inverters has been provided focusing on the performance and the number of components. Finally, the performance of the proposed inverter has been simulated utilizing PSCAD/EMTDC software package.